2021
DOI: 10.3389/fmed.2021.774691
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes and Prognostic Predictors in Patients With Malignant Struma Ovarii

Abstract: Background: Malignant struma ovarii (MSO) is an extremely rare ovarian malignant tumor and there is limited data on the survival outcomes and prognostic predictors of MSO. The objectives of this study were to investigate the disease-free survival (DFS), overall survival (OS), and disease-specific survival (DSS) rates of patients with MSO, and also evaluate the prognostic factors in this population.Methods: A retrospective study was conducted and 194 cases of MSO were selected. DFS was assessed by the logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…SO is a highly specialized form of mature ovarian teratoma consisting of thyroid tissue showing all histological features of the thyroid gland. Depending on the histologic features, struma ovarii can be classified as benign or malignant; the diagnostic criteria for MSO are similar to those for differentiated thyroid cancer [ 4 , 10 , 11 , 14 ]. Features indicative of malignancy include cytologic atypia, nuclear grooves, “ground-glass” overlapping nuclei, increased mitotic activity, and vascular invasion [ 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SO is a highly specialized form of mature ovarian teratoma consisting of thyroid tissue showing all histological features of the thyroid gland. Depending on the histologic features, struma ovarii can be classified as benign or malignant; the diagnostic criteria for MSO are similar to those for differentiated thyroid cancer [ 4 , 10 , 11 , 14 ]. Features indicative of malignancy include cytologic atypia, nuclear grooves, “ground-glass” overlapping nuclei, increased mitotic activity, and vascular invasion [ 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sijian et al demonstrated an excellent survival outcome in patients with MSO irrespective of the treatment strategy. Advanced stage disease (stage IV), age more than 55 years and poorly differenced tumour were independent risk factors of prognosis in patients with MSO [ 14 ]. Similarly, Cui et al reported a 4.72% mortality rate among 127 patients and most of the death occurred in patients with distant metastasis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, RAI was widely recommended in metastatic MSO for ablation of residual diseases [ 25 , 26 , 28 ], and it may be the only practical therapeutic option in patients with unresectable diseases, such as multiple liver, lung, or bone metastases [ 29 ]. Although the exact therapeutic response rate for RAI in MSO was unavailable due to the extreme rarity and most patients received both surgery with RAI [ 15 ]. Some patients achieved stable diseases or complete remission with RAI therapy alone [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors raised the possibility that the size of the carcinomatous component rather than the size of the strumal component might have a prognosticative value in patients with MSO 12. Other poor prognostic findings that have been proposed include the presence of adhesions, ascites of 1 L or more, and ovarian serosal rent27 or FIGO stage IV disease, age 45 years or older, and poorly differentiated tumour 29. One study did not identify any potential risk factors in MSO confined to the ovary 12…”
Section: Discussionmentioning
confidence: 99%